PENGELOLAAN TINDAK LANJUT PENGADUAN MASYARAKAT PADA SIARAN â€œKABAR BUPATIKUâ€ DI KABUPATEN TEGAL - Etkisyan, Johan Arifin; Manar, Dzunuwanus Ghulam (Journal of Politic and Government Studies, 2018)
Follow-up is an activity undertaken in the framework of completing the management of public complaints. Community complaints management in Tegal District is conducted through the process of receiving, recording, reviewing, distributing, confirmation, clarification, research, inspection, reporting, follow-up, and archiving. The substance of the public complaint consists of: the substance of public complaint is supervised and the substance of publicÂ complaintÂ that is not supervised.The research method used is qualitative research method with explorative research type. Data collection technique used is interview, documentation, and literature study. The informants in this research are LPPL Tegal Radio Slawi Ayu FM (Director & Host of